Servants and Masters in 18th-Century France : the Uses of Loyalty. - Maza, Sarah C., 1953- (Princeton legacy library., 2014)
Here is the first major study of domestic service in France from the late seventeenth century to the early nineteenth century, describing its transformation from a male-oriented occupation, aristocratic in style and often geared to public display, to one that was female, middle-class, and centered on the household. Originally published in 1984. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the orig.